WOMEN AND EDUCATION IN HISTORIA VULGAR, BY RAFAEL DELGADO - Vera Ponce, Salvador (2021)
This article analyzes the work Historia vulgar, by Rafael Delgado, in the light of the ideas of Mílada Bazant, to demonstrate that its realism is effective in explaining the overcoming of the conflict between traditional and modern educational models, through the participation of women in education and the use of human virtues. In this narrative there are two determining structural elements: the woman and the urgency of a historiographic change, which cannot come from a traditional education. But it is also evident that the sadness of Mexicans originates from an inadequate modern education that instead of cheering and uniting Mexicans divides them and plunges them into poverty. In vulgar history, there is a plausible one that corresponds to the Porfirian society of the second half of the nineteenth century, but that has much meaning today.